Speed/Torque Estimation and Control of a DC Machine in Four Quadrants Operation Modes - Antar, Rakan Khalil (Al-Nahrain Journal for Engineering Sciences, 2018)
Transfer function characteristics of a DC machine are used in this paper to estimate speed and torque in four quadrant operation modes. Estimation speed and torque control based on a DC machine transfer function is implemented by measuring the DC chopper instantaneous average output voltage and current. MATLABis used to implement the DC drive circuit in the forward and reverse motoring and regenerative modes, respectively. The DC drive system is simulated at different speed and load torque values in steady state and dynamic operating conditions. Simulation results demonstrate success of the sensorless and PI controller systems, which gives satisfactory agreements between the estimated, actual and reference speed and torque values.